The Role of Proverbs of the Qur'an in Transmitting Islamic Education Values - Siti Nurfaizah; Achmad Abubakar; Hamka Ilyas (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Amsalul Qur’an, or Qur’anic parables, represent a unique rhetorical form in the Qur’an that conveys deep symbolic meanings aimed at delivering moral and spiritual messages in a persuasive and emotionally resonant way. The complexity of meaning within Qur’anic parables demands interpretive approaches that are not only textual but also contextual and multidisciplinary. This research is motivated by the need for an Islamic educational model that is more communicative and reflective of contemporary societal conditions. The aim of this study is to identify the strategic role of Amsalul Qur’an in conveying Islamic educational values and to evaluate its implications for meaningful learning processes. The study employs a qualitative approach with content analysis of parabolic verses in the Qur’an, along with a review of tafsir literature, Islamic education theories, and educational communication frameworks. The findings reveal that Amsalul Qur’an functions as an effective narrative bridge in internalizing the values of monotheism, justice, patience, and social responsibility. The study recommends integrating the amsal approach into Islamic education methodologies to foster more reflective, dialogical, and transformative learning experiences. Thus, Amsalul Qur’an holds strategic potential as an instrument in character building and the strengthening of students’ spirituality in the modern era.